Normal Systolic Blood Pressure at Presentation With Acute Ischemic Stroke Predicts Cardioembolic Etiology - Moores, Margaret (J Am Heart Assoc, 2020)
BACKGROUND: Early insight into the possible etiology of ischemic stroke allows for early initiation of mechanism‐specific secondary stroke prevention. Initial systolic blood pressure during acute ischemic stroke may relate to stroke etiology. We sought to determine whether normotension at presentation with acute ischemic stroke predicts cardioembolic etiology. METHODS AND RESULTS: All patients presenting with acute ischemic stroke within 12 hours of symptom onset at a comprehensive stroke center from January 2015 to December 2017 were assessed. Normotension was defined as systolic blood pressure ≤130 mm Hg. The primary exposure was blood pressure on arrival at the hospital, and the primary outcome was cardioembolic etiology. Multivariable regression with stepwise selection was used to adjust for relevant covariates. We included 683 patients in our analysis, 303 (44%) of whom were diagnosed with cardioembolic etiology at 6 months. The probability of cardioembolic etiology was inversely associated with systolic blood pressure, and initial systolic blood pressure was significantly associated with cardioembolic etiology (odds ratio: 1.15; 95% CI, 1.05 to 1.26). Normotension was associated with 2.62‐fold increased odds of cardioembolic etiology (95% CI, 1.46 to 4.72). CONCLUSIONS: Normotension at presentation with acute ischemic stroke strongly predicts cardioembolic etiology. These patients may especially benefit from early and prolonged cardiac investigations.